Integration of multiple ultra-capacitor banks in DC microgrid part II - Foo, Kai Ting (2019)
The main objective of this final year project is to achieve quality power output in the system through the integration of multiple ultracapacitor banks into the DC microgrid. However, ultracapacitor is an energy storage (ES) with high power density but low energy density. Using ultracapacitor alone would not be able to cover all the loads and maintain long term operations. Therefore, ultracapacitor can be integrated with low power density battery to form a hybrid energy storage system (HESS). With HESS, an energy management system (EMS) is used to realise dynamic power sharing. This project will study on the different control algorithms to manage the different kind of ESs in a HESS within a DC microgrid. In this project, the control algorithms are realised by filter-based decentralised control. The net power of the system is passed through the high or low pass filters to generate power references for the different ESs. Conventional VP droop control is used on battery which has limited response and high energy density. A proposed integral-droop (ID) control is used on ultracapacitor to compensate transient power at high frequencies. Aside from the HESS, a DC/DC boost converter is included as an interface to simulate the DC microgrid. All the simulations carried out are done in MATLAB Simulink.